Financial burden imposed on the insured patients for private treatment: Evidence from a state of Iran - Manal Etemadi; Mohammad Shiri; Elham Rostami; Mohammad Mohseni; Masumeh Seyedi (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Protection against financial risks is one of the important goals of the health system. The present study aims to determine the rate of exposure to catastrophic expenditures in the insured inpatients. METHODS: The present study was cross-sectional one which is conducted in 2016. The statistical population comprised all the insured patients presenting to a private hospital in Qom who presented to the hospital within 4 months from December 2015 to March 2016. Random convenience sampling method was used, and the sample size was estimated at 267 people using Cochran formula. A questionnaire was employed for data gathering. Data were analyzed using Chi-square test and logistic regression using SPSS software version 20. RESULS: Patients exposed to catastrophic expenditures of treatment accounted for the 54.8% of the cases. The highest rate of being exposed to the catastrophic expenditures was related to the insured patients of the Universal Health Insurance Fund (UHIF). People with rural insurance, on average, paid the highest cost of treatment in the hospital. The surgical ward and critical care unit accounted for the biggest percentage of the patients who incurred catastrophic expenditures. Being rural, longer length of stay, lower education of the head of the household, lack of supplementary insurance coverage, and being in UHIF coverage have a substantial relationship with being exposed to catastrophic expenditures. DISCUSSION: The socioeconomic status of the insured people in the UHIF and the Rural Insurance Fund was worse than other funds in terms of less utilization and higher rate of exposure to catastrophic expenditures, and this issue requires the adoption of specific targeted policies for these groups in respect with reducing out-of-pocket payments through mechanism such as stepwise copayments, maximum out-of-pocket limit, fee exemptions or waiver and providing supplementary insurance to reduce the exposure to catastrophic expenditures.